Peran Perpustakaan Sekolah Dalam Meningkatkan Literasi Informasi Siswa: Studi Kasus di SMP Swasta Ira Medan - Margolang, Ade Irvan; Nasution, M Rezi Syahbanda; Nasution, Abdul Fattah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to explore the role of school libraries in improving students' information literacy at SMP Swasta IRA Medan. Using a quantitative survey method, data were obtained through a questionnaire involving 50 students as respondents. The results showed that the frequency of students' visits to the library was still low, with most respondents visiting the library less than once a week. Although the book collection was considered relevant, students provided input regarding updating and improving the collection. Library facilities and services also need improvement to increase the attractiveness of the library. This study recommends the addition of digital facilities, the implementation of literacy programs, and active promotion to increase library utilization. Thus, the library can function optimally as a center for information literacy resources.